The digital transformation program management in medium-sized businesses: a network approach - Anshin, Valery; Bobyleva, Alla (Serbian Journal of Management, 2021)
The article deals with the process management’s issues of digital transformation in companies. The emphasis is made on the consideration of program’s projects as interrelated components with the features of emergency system, not as a weakly interconnected complex (linear set) of projects. Authors propose the organizational model of transformation’s program management and the new approach to prioritizing projects based on the use of network analysis. The suggested method allows to evaluate the role of the project in the transformation program and its impact on the other projects, as well as its impact on the planned benefits of the program. It also allows to distribute resources between projects and to assess the risks of the program as a whole. The article focuses on the differences of medium-sized companies’ management methods, on the one hand, from companies in small business, and on the other hand, from large companies. The application of the method was tested at a medium-sized poultry farm. The analysis of projects of the real program was made, the network model of the program was built, and the probability of projects’ and the program at all success was estimated. The evaluation of the program indicators allowed the authors to make conclusions about priorities of separate projects. The proposed approach can be used in various companies, regardless of industry affiliation.